50th Celebratory Volume. - Polachek, Solomon W. (Research in labor economics., 2023)
This 50th Celebratory Research in Labor Economicsvolume contains ten original and innovative articles each written by stellar senior scholars in labor economics addressing aspects of worker well-being.